Pengaruh Derivatif Keuangan dan Tax Avoidance terhadap Pengungkapan Pajak pada Perusahaan Manufaktur - Ananda Liana Putri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
One of the factors that determine the occurrence of tax avoidance is financial derivatives. That is because the tax regulations in Indonesia on derivative transactions are still very weak and often debated. The lack of clarity of tax regulations on derivative transactions can also be used by companies to conduct tax avoidance. This can certainly harm state revenues, especially revenues from the tax sector. Disclosure of corporate tax information encourages increased tax compliance. Therefore, the level of corporate tax disclosure is associated with tax avoidance. This study aims to test and analyze the effect of financial derivatives and tax avoidance on tax disclosure. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2022. By using purposive sampling method, obtained from several samples of companies that meet the criteria. This study uses secondary data which is then processed using the SmartPLS 4.0 program.